Using reproductive hormones extracted from archived muscle tissue to assess maturity and reproductive status in porbeagles Lamna nasus - Anderson, Brooke N.; Kaloczi, Juliana; Holden, Courtney; Einig, Amanda; Donaldson, Linda; Malone, Hunter; Passerotti, Michelle S.; Natanson, Lisa J.; Bowlby, Heather D.; Sulikowski, James A. (Frontiers in Marine Science, 2023)
While lethal sampling can be the most effective technique to collect critical reproductive data for elasmobranchs, non-lethal techniques need to be validated for future use. Concentrations of reproductive hormones in plasma and muscle have been found to correlate to sexual maturity and/or reproductive cycles in oviparous as well as yolk-sac, placental, and histotrophic viviparous elasmobranchs, offering a potentially non-lethal technique to study reproduction. However, reproductive hormone analysis is scant for oophagous sharks. This study utilized muscle tissues from porbeagles Lamna nasus that were dissected for other life history studies and were stored frozen for up to 37 years to quantify testosterone (T) and estradiol (E2) concentrations in relation to previously-known maturity and reproductive stage. A total of 207 samples (92 males, 115 females) from porbeagles ranging in size from 80 to 256.5 cm fork length were analyzed. Muscle T and E2 concentrations were related to maturity and reproductive stage in porbeagles, with the highest T concentrations found in mature males during the spermatogenic season (summer) and the highest E2 concentrations found in gravid females. These results suggest muscle hormone concentrations have the potential to serve as a non-lethal proxy of reproductive stage in oophagous sharks. This study also demonstrates the value of specimen sharing and the potential for continued use of stored vertebral muscle tissue for reproductive hormone analysis in order to optimize the amount of data gained from biological samples. Future use of these methods would be particularly valuable for threatened species for which lethal sampling is restricted.